Blood Women in Perspective of Fiqh Syafi’iyyah and Medical Science - Abdullah; Mustafa Kamal; Siti Zalikha; Sadiqul Wahdi; Muhammad Ikbal (Britain International for Academic Research (BIAR) Publisher, 2019)
Changes in the menstrual period (menstrual cycle) because of changes in the cycle have an impact on the legal status of blood that comes out. According to Syafi'iyyah Fiqh when blood comes out for a longer time due to excessive bleeding caused by contraception it will become khiyar between menstrual blood or istihadhah blood, whereas in medical science there is no term istihadhah for women, only menstrual blood and puerperal blood. Researchers try to raise this issue as material that deserves to be studied in depth, with the title